Analysis of risk factors for autoimmune thyroid disease based on blood indicators and urinary iodine concentrations - Liu, Jianning; Feng, Zhuoying; Gao, Ru; Liu, Peng; Meng, Fangang; Fan, Lijun; Liu, Lixiang; Du, Yang (Frontiers in Endocrinology, 2024)
Objective: The aim of this study was to elucidate the relationships between thyroid hormones, lifestyle factors, biochemical markers, and autoimmune thyroid disease (AITD), thereby identifying the factors influencing the development of these diseases.Methods: The study encompassed 517 patients with AITD and 549 patients with non-autoimmune thyroid disease. Demographic and clinical data were collected, and various laboratory indicators, including urinary iodine and thyroid hormones, were measured and compared between the groups. Lasso regression was employed to select the independent variables, while logistic regression analysis determined the factors associated with the development of AITD.Results: The prevalence of drinking alcohol history, median urinary iodine, and TSH concentrations proved significantly greater in the AITD group compared to the control group, while FT3 levels demonstrated lower values within the AITD group (p<0.05). Furthermore, there was a significant difference in the distribution of iodine nutrition status between the two groups (p<0.05). Both univariate and multivariate logistic regression analyses revealed significant associations among excessive iodine intake, drinking alcohol history, TSH, FT3, and the development of AITD.Conclusions: Excessive iodine intake and drinking alcohol history are implicated in an augmented risk of developing AITD. The prevention of AITD may necessitate the regular monitoring of TSH and FT3 concentrations.